2004
DOI: 10.1161/01.hyp.0000146908.75091.99
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor Induces Tissue Factor Expression in Vascular Smooth Muscle Cells via Activation of Egr-1

Abstract: Abstract-Activation of vascular smooth muscle cells (SMCs) by platelet-derived growth factor (PDGF) is a seminal event in the initiation and progression of the atherosclerotic lesion and may contribute to atherosclerotic plaque instability with plaque rupture and thrombus formation. Tissue factor (TF), a prothrombotic molecule expressed by various cell types within atherosclerotic plaques, is thought to play a major role in thrombus formation after plaque rupture. This study examined intracellular signaling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 39 publications
5
27
0
2
Order By: Relevance
“…The role of phosphorylation of Egr-1 remains controversial (Cao et al, 1993;Jain et al, 1996;Huang et al, 1998;Kamimura et al, 2004). We recently observed that curcumin reduced the level of phosphorylation of Egr-1, which was mimicked by a specific MEK inhibitor (data not shown here).…”
Section: Discussionsupporting
confidence: 47%
“…The role of phosphorylation of Egr-1 remains controversial (Cao et al, 1993;Jain et al, 1996;Huang et al, 1998;Kamimura et al, 2004). We recently observed that curcumin reduced the level of phosphorylation of Egr-1, which was mimicked by a specific MEK inhibitor (data not shown here).…”
Section: Discussionsupporting
confidence: 47%
“…PDGF, mainly expressed in VSMCs and endothelial cells, promote mitosis and play an important role in the proliferation of VSMCs [6][7][8]37]. The binding of PDGF-BB, a subtype of PDGF released from injured vessels, to its receptor can trigger the activation of downstream and then contribute significantly to VSMCs proliferation [9][10][11][12]. In this paper, PDGF-BB could effectively induce MOVAS proliferation, which was consistent with the previous studies reported.…”
Section: Discussionsupporting
confidence: 88%
“…Platelet-Derived Growth Factor (PDGF) is an important regulator that stimulates the proliferation of VSMCs [6][7][8]. The binding of PDGF-BB, a subtype of PDGF, to its receptor triggers the activation of downstream signaling molecules such as Mitogen-Activated Protein Kinases (MAPKs) to promote VSMCs proliferation and growth [9][10][11][12][13]. Therefore, preventing the PDGF-BB induced VSMCs proliferation might be a promising strategy for treating the development of neointima in atherosclerosis and post-angioplasty restenosis in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In human vascular smooth muscle cells, p38 and PI3-kinase mediate thrombin-induced TF expression. 26 In rat vascular smooth muscle cells, ERK is involved in TF expression to lysophosphatidic acid 28 and PDGF-BB, 25 whereas p38 and PI3-kinase do not play a role. Hence, the effect of MAP kinases and the PI3 kinase pathway appears to depend on the particular stimulus and/or the species involved.…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%